THE FORMATION AND ACQUISITION OF KNOWLEDGE OF THE ELITE SOCCER COACHES OF COSTA RICA TO TRAIN AND COACH - Rivas-Borbón, Oscar Milton (2018)
This study aimed to explore the aspects related to the formation and sources of knowledge that Costa Rican elite soccer coaches have in order to coach and train, and how those aspects influence the decision-making process of soccer coaches’ in their sport environment. For this purpose, a qualitative research project has been carried out, where data was collected through the method specifically known as methodological triangulation, which consisted in the application of two methodological tools, the interview and the questionnaire, whose final results were compared with each other. The study population consisted of 10 coaches of the Costa Rican First Division Soccer League. The results indicate that coaches base their work of coaching and training on almost all subcategories of acquisition of knowledge that were raised in the study. However, the subcategories of experience as a player, professional experience, and the use of technological tools were assigned a greater value, especially regarding the field of coaching in competition. At the same time, the subcategory interaction between colleagues was assigned the lowest value. The conclusions of the study should be analyzed when designing curricula in the training of soccer coaches.